Efficacy of sorafenib plus transcatheter arterial chemoembolization in treating hepatocellular carcinoma with portal vein tumor thrombosis: A meta-analysis - Xu Li; Chen Shanshan; Cao Haijun; Feng Zemin; Yang Chao (Acta Pharmaceutica, 2024)
This meta-analysis aimed to evaluate the efficacy of sorafenib plus transcatheter arterial chemoembolization (TACE) in treating hepato-cellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT). Twelve randomized controlled trials published until 28th Sep 2022 were finally included. Of the total 1746 patients, of whom 458 received sorafenib and TACE treatment (Group S+TACE), and 1288 only underwent TACE (Group TACE), were enrolled. Outcomes including time to progression (TTP), objective response rate (ORR), disease control rate (DCR), overall survival (OS), survival rate (SR), and adverse reactions, were extracted. The OS (HR: 0.596, 95 %CI: 0.507–0.685, p < 0.001; I2 = 0.0 %) and TTP (HR: 0.379, 95 %CI: 0.205–0.553, p < 0.001; I2 = 4.5 %) in the S+TACE group were longer than those in the TACE group. The ORR (RR: 2.101, 95 %CI: 1.555–2.839, p < 0.001; I2 = 0.0 %), DCR (RR: 1.547, 95 %CI: 1.126–2.126, p = 0.007; I2 = 79.6 %) and SR (RR: 1.416, 95 %CI: 1.183-1.694, p < 0.001; I2 = 83.8 %) in the S+TACE group were higher than those in the TACE group. Compared with the TCAE group, the higher odds of HFSR, oral ulcer, and diarrhea among patients with HCC complicated by PVTT were discovered in the S+TACE group. The marginal significance was found in ascites and gastrointestinal bleeding between the two groups. Sorafenib plus TACE has good efficacy and mild adverse reactions, which may be worthy of clinical promotion.